Nontraditional Student Admission, Support and Retention in Undergraduate Programs - Jorgelina Abbate Vaughn (Universidad Autónoma de Madrid, 2018)
This article describes the support measures that universities, with democratic educational objectives and ample access, should provide to ensure an ideal context which maximizes recruitment, retention and graduation of nontraditional students (NTE). These students come from ethnic minorities, come from harsh economical conditions (first generation to go to university), students who switch majors and several other handicaps. The support mechanisms studied in this article make up a model that includes the institutional processes needed to help students who gain access to a university without the command of the skills needed for academic success. This lack of skills is typically expressed in reading writing and study habits. At the same time, an argument is presented in which this model must be based in a profound vision of social justice and promoting post secondary education for NTE, who have not traditionally benefited from such opportunities